In situ and atomic-scale investigations of the early stages of γ precipitate growth in a supersaturated intermetallic Ti-44Al-7Mo (at.%) solid solution. (1st February 2019) - Erdely, Petra; Staron, Peter; Stark, Andreas; Klein, Thomas; Clemens, Helmut; Mayer, Svea
Abstract: Intermetallic β-stabilised γ-TiAl based alloys offer novel opportunities for microstructural design. This paper investigates the growth behaviour of γ precipitates from a supersaturated βo matrix in a β-homogenised Ti-44Al-7Mo (at.%) alloy. Combining in situ high-energy X-ray diffraction and small-angle scattering at a synchrotron radiation source with atom probe tomography as a direct imaging technique, the early stages of γ precipitate growth are characterised for the first time. The results show that the βo → γ phase transformation occurs without the formation of an intermediate phase. At a heating rate of 10 K·min −1, first diffusional processes that can be ascribed to the βo → γ phase transformation commence at about 450 °C. Elemental redistribution controls the growth of the γ precipitates, which is connected with the introduction of misfit-induced strain fields around the initially coherent γ particles. Further heating results in the loss of coherency between the disc-shaped γ precipitates and the βo matrix. The presented findings advance the fundamental understanding of the βo → γ phase transformation in γ-TiAl based alloys and provide quantitative data for the design of refined microstructures in the course of technological heat treatments. Graphical abstract: Image 1